Studi Cemaran Cendawan Pasca Panen Pada Emping Melinjo di Kabupaten Serang - Rida Oktorida Khastini; Nani Maryani; Indria Wahyuni; Nadya Pratiwi Tri Lantafi (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
Emping Melinjo is a typical Banten Food made from melinjo seed. This research aimed to study fungi that contaminate Emping Melinjo. Samples were collected from two melinjo producers and distributors in Kabupaten Serang; Waringinkurung and Ciomas. Samples were isolated with PDA medium. Isolates were identified from its macroscopic and microscopic characters. 11 fungi were successfully isolated, namely Aspergillus, Basipetospora, Paecilomyces, Rhizopus, Cladosporium, Fusarium, and Candida. The largest dominance index was the genus Aspergillus with 3.44. Fusarium, Basipetospora, and Cladosporium have dominance index of 0.81 followed by Paecilomyces and Rhizopus for 0.02. The highest contamination intensity of 26.8% in the Ciomas producer, 3.12% in the Ciomas distributor. 1.2% at Waringinkurung producers, and 2.4% Waringinkurung distributors.